2017
DOI: 10.1097/nna.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Nurse Work Environment and Patient Safety Culture on Attitudes Toward Incident Reporting

Abstract: OBJECTIVE The aim of this study was to explore the influence of nurse work environments and patient safety culture on attitudes toward incident reporting. BACKGROUND Patient safety culture had been known as a factor of incident reporting by nurses. Positive work environment could be an important influencing factor for the safety behavior of nurses. METHODS A cross-sectional survey design was used. The struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 15 publications
4
34
0
2
Order By: Relevance
“…Risk is subjective; however, it is essential that the concerns raised by nurses are not dismissed and that there is an exploration of the existing wide variation in what is considered risky behaviour. Reports in our study influenced transparency of decision‐making, which were related to the belief that patient safety would be improved by reporting incidents (Yoo & Kim, 2017).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Risk is subjective; however, it is essential that the concerns raised by nurses are not dismissed and that there is an exploration of the existing wide variation in what is considered risky behaviour. Reports in our study influenced transparency of decision‐making, which were related to the belief that patient safety would be improved by reporting incidents (Yoo & Kim, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…Within nursing, differences exist between safety‐related issues and nursing hierarchy. Yoo and Kim (2017) reported that nurses with less than 3 years’ experience (staff nurses) rated risk on a higher scale compared to nurses with 4–6 years of clinical experience. Murray, Sundin, and Cope (2019) report that newly qualified graduate nurse does not have confidence to manage some patient safety situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their importance, there are no studies analysing how EI and empathy can affect attitudes towards communication or comparing the effect of the emotional component (empathy and EI) and attitudes on communication behaviour. Additionally, some studies have used only regression models in nursing context (Chang et al., ; Yoo & Kim, ), ignoring interactions and how different paths could lead to the same result, as could be assessed using qualitative comparative analysis models (QCA) (Blackman, Wistow, & Byrne, ). The linear models (regressions) focused on the individual contribution of each variable, while QCA prioritise the importance of variable combinations (Ragin, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are studies of nursing focused on analysing communication: communicative errors generate anxiety, misunderstandings, complications, delayed treatments and prolonged hospital stays (Hemsley et al, 2001), destructive conflicts among nurses (Kim, Nicotera, & McNulty, 2015). Adequate communication improves patients' well-being, quality of life, and satisfaction with care (McGilton et al, 2012) and nurses' satisfaction with their work (Chan, Jones, Fung, & Wu, 2012), teamwork and burnout levels (Nadzam, 2009 (Chang et al, 2017;Yoo & Kim, 2017), ignoring interactions and how different paths could lead to the same result, as could be assessed using qualitative comparative analysis models (QCA) (Blackman, Wistow, & Byrne, 2011). The linear models (regressions) focused on the individual contribution of each variable, while QCA prioritise the importance of variable combinations (Ragin, 2008).…”
Section: Introductionmentioning
confidence: 99%